2023
DOI: 10.1038/s41598-023-40431-y
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of neural mechanotransduction response in human traumatic brain injury organoid model

Susana M. Beltrán,
Justin Bobo,
Ahmed Habib
et al.

Abstract: The ability to model physiological systems through 3D neural in-vitro systems may enable new treatments for various diseases while lowering the need for challenging animal and human testing. Creating such an environment, and even more impactful, one that mimics human brain tissue under mechanical stimulation, would be extremely useful to study a range of human-specific biological processes and conditions related to brain trauma. One approach is to use human cerebral organoids (hCOs) in-vitro models. hCOs recre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…The objective of our study was to investigate the protective effect of TGF-β1 on mechanically injured neurons using an in vitro neuronal scratch cell model and explore its molecular mechanism. This cellular model, which is based on mechanical injury to primary cultured neurons, has been used in numerous studies and provides an essential tool for the treatment of TBI ( Ni et al, 2019 ; Beltrán et al, 2023 ; Wang et al, 2024 ), that can reproduce neurological injuries such as stab wounds, penetrating skull frcatures, and gunshot that result in transection of the cell body ( Morrison et al, 1998 ). We found that treatment with TGF-β1 (10 ng/mL) for 24 h significantly inhibited LDH release induced by mechanically injured cortical neurons and reduced cytotoxicity in our in vitro model, consistent with our previous findings ( Li et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The objective of our study was to investigate the protective effect of TGF-β1 on mechanically injured neurons using an in vitro neuronal scratch cell model and explore its molecular mechanism. This cellular model, which is based on mechanical injury to primary cultured neurons, has been used in numerous studies and provides an essential tool for the treatment of TBI ( Ni et al, 2019 ; Beltrán et al, 2023 ; Wang et al, 2024 ), that can reproduce neurological injuries such as stab wounds, penetrating skull frcatures, and gunshot that result in transection of the cell body ( Morrison et al, 1998 ). We found that treatment with TGF-β1 (10 ng/mL) for 24 h significantly inhibited LDH release induced by mechanically injured cortical neurons and reduced cytotoxicity in our in vitro model, consistent with our previous findings ( Li et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%